Sediment Variation Along The East Coast of a Peninsular Malaysia - Mamat, Mustafa; Mat Amin, Abd Rahman; Ahmad, Fadhli; Mamat, Mustafa (2013)
The northeast monsoon season (NEMS), which occurs between November and March every year, brings heavy rains and strong wind to the east coast of Peninsular Malaysia. Large sediment resuspension during this season is caused by high waves and river discharge carried by the river to the sea. Sediment is defined in this research as both organic and inorganic materials. Remote sensing reflectance (R ) of the Moderate Resolution Spectroradiometer (MODIS) 667 nm channel is used in this study as a Total Suspended Sediment (TSS) index. The data was acquired from Aqua satellite with 9 km resolution. The study was conducted along the eastern coast of Peninsular Malaysia over the period of 2002- 2012. The result shows that TSS along the Peninsular Malaysia coastline and the river mouth is highly seasonal. The highest TSS is observed during NEMS with the peak value in November-December every year.